(untitled) (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
This study aims to analyze the effectiveness of the implementation of the Community-Based On-site Domestic Wastewater Grant Program in Teladan Village, Curup Selatan District, Rejang Lebong Regency. The program is intended to improve access to safe and adequate sanitation, particularly for low-income communities. The research employs a descriptive qualitative approach, using Riant Nugroho’s policy effectiveness theory, which includes five aspects: policy accuracy, implementation accuracy, target accuracy, environmental suitability, and process accuracy. Data were collected through interviews, observation, and documentation involving village government officials, program implementers, and beneficiary communities. The results show that the program has successfully provided sanitation facilities that meet technical standards, significantly reducing open defecation practices. Positive impacts are also seen in the improved quality of life and public awareness of sanitation issues. However, several challenges remain, such as limited community understanding of proper maintenance, reluctance to change old habits, and a lack of labor during the construction phase. Therefore, continuous education and reinforcement of human resources are essential to ensure the program’s long-term effectiveness and sustainability.